2016
DOI: 10.14737/journal.jap/2016/3.1.10.15
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Studies of Fascioliosis (Fasciola gigantica Infection) in Cattle

Abstract: To investigate the epidemiology of fascioliosis in cattle of different ages, sexes, seasons and different district in Sylhet division of Bangladesh. Epidemiological studies on fascioliosis of cattle were under taken in such localities under different climatic conditions existing in Sylhet division of different district. Cattle were divided into young and adult groups. Rectal fecal samples from household live and livers from slaughterhouse cattle were collected randomly and examined by direct/and sedimentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
1
9
1
1
Order By: Relevance
“…The rate of Fasciola spp. infection reached 48%, higher than in previous studies that found rates of 3.28% in Iran [24] and 22.17% in Bangladesh [25]. However, it was lower than reported by Ashraf et al , indicating that Fasciola spp.…”
Section: Discussioncontrasting
confidence: 61%
“…The rate of Fasciola spp. infection reached 48%, higher than in previous studies that found rates of 3.28% in Iran [24] and 22.17% in Bangladesh [25]. However, it was lower than reported by Ashraf et al , indicating that Fasciola spp.…”
Section: Discussioncontrasting
confidence: 61%
“…As buffaloes inhabit wetter areas the prevalence of fascioliasis is expected to be higher than other ruminant species [5052]. Previous published reports from Bangladesh have also reported similarly higher prevalence in cattle and buffalo than goats and sheep [14, 22, 28, 33]. However, the mortality was relatively higher in goats (33 per 10,000) than other species (8–25 per 10,000).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of fascioliasis in slaughtered animals has been reported to be 15–66% in cattle [14, 28], 3.8–22% in goats [17, 29–31], 81% in sheep [32] and 23–47% in buffaloes [22, 33], respectively. The actual burden of fascioliasis - including subclinical disease - is likely much higher than that reported above [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penularan Schistosomiasis, menurut Hu et al (2017) negara lain pun berkisar antara 386% (Islam et al 2016;Karim et al 2015;Khoramian et al 2014;Bedada et al 2017;Elkhatam & Khalafalla 2016;El-Tahawy et al 2017;Elshraway & Mahmoud 2017;Hussein & Khalifa 2010;Hassan et al 2017;Elliott et al 2015;Pandya et al 2015;Yadav et al 2015). Infeksi oleh Fasciola gigantica pada sapi dan kerbau di Indonesia pada studi ini dapat terjadi berkaitan dengan kondisi iklim yang memungkinkan perkembangbiakan inang antaranya, yakni keong Lymnea rubiginosa (Widjajanti 2004).…”
Section: Schistosoma Japonicum: Prevalensi Dan Intensitas Infeksiunclassified